Photophysical Analysis of the Formation of Organic–Inorganic Trihalide Perovskite Films: Identification and Characterization of Crystal Nucleation and Growth - Anaya, Miguel (J Phys Chem C Nanomater Interfaces, 2016)
[Image: see text] In this work we demonstrate that the different processes occurring during hybrid organic–inorganic lead iodide perovskite film formation can be identified and analyzed by a combined in situ analysis of their photophysical and structural properties. Our observations indicate that this approach permits unambiguously identifying the crystal nucleation and growth regimes that lead to the final material having a cubic crystallographic phase, which stabilizes to the well-known tetragonal phase upon cooling to room temperature. Strong correlation between the dynamic and static photoemission results and the temperature-dependent X-ray diffraction data allows us to provide a description and to establish an approximate time scale for each one of the stages and their evolution. The combined characterization approach herein explored yields key information about the kinetics of the process, such as the link between the evolution of the defect density during film formation, revealed by a fluctuating photoluminescence quantum yield, and the gradual changes observed in the PbI(2)-related precursor structure.